Pelvic Hydatid Cyst with Hydroureteronephrosis: A Rare Case Report - Amir Mohammad Salehi; Hossain Salehi; Ensiyeh Jenabi (Case Reports in Infectious Diseases)
Hydatid cyst is a parasitic disease caused by Echinococcus granulosus or Echinococcus multilocularis. Humans are accidentally infected with the parasite. The cyst is usually found in the liver and lungs and rarely occurs in other body parts. The present article describes a rare case of pelvic hydatid cyst in a young man who presented with nausea, vomiting, and right abdominal pain. Two large cystic masses were discovered during a CT scan in the patient’s pelvic region, resulting in right urinary tract hydroureteronephrosis. Additionally, the antibody index was used to confirm the presence of a primary hydatid cyst.